2016
DOI: 10.1002/cphc.201600308
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembly of the Cyclic Lipopeptide Daptomycin: Spherical Micelle Formation Does Not Depend on the Presence of Calcium Chloride

Abstract: The cyclic lipopeptide Daptomycin, used as a treatment for infections where antimicrobial resistance is observed, is shown to self-assemble into spherical micelles above a critical aggregation concentration. Micelles are observed either in the absence or presence of CaCl2 , in contrast to claims in the literature that CaCl2 is required for micellization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 22 publications
0
32
1
1
Order By: Relevance
“…Accumulated evidences suggest that by inserting of its hydrophobic decanoyl chain into bacterial membrane, daptomycin causes membrane permeabilization and potassium ions outflow, leading to rapid bacteria cell death . The formation of spherical micelles by daptomycin has been proposed to facilitate bacterial‐targeted delivery . However, studies also shown that >90% of the total amount of daptomycin in blood is protein‐bounded, which in turn, may affect its antibacterial activity, as demonstrated in protein‐free media .…”
Section: Clinical and Preclinical Examples Of Amphiphilic Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulated evidences suggest that by inserting of its hydrophobic decanoyl chain into bacterial membrane, daptomycin causes membrane permeabilization and potassium ions outflow, leading to rapid bacteria cell death . The formation of spherical micelles by daptomycin has been proposed to facilitate bacterial‐targeted delivery . However, studies also shown that >90% of the total amount of daptomycin in blood is protein‐bounded, which in turn, may affect its antibacterial activity, as demonstrated in protein‐free media .…”
Section: Clinical and Preclinical Examples Of Amphiphilic Drugsmentioning
confidence: 99%
“…[111] The formation of spherical micelles by daptomycin has been proposed to facilitate bacterial-targeted delivery. [112] However, studies also shown that >90% of the total amount of daptomycin in blood is protein-bounded, [113,114] which in turn, may affect its antibacterial activity, as demonstrated in protein-free media. [115] Yet these in vitro protein binding studies failed to predict clinical efficacy of daptomycin, suggesting other important characteristics, such as favorite pharmacokinetics are of vital clinical importance to the success of antibiotic therapy.…”
Section: Amphiphilic Peptidesmentioning
confidence: 99%
“…The paper also showed that the PA can also be transported across the blood-brain barrier [52]. One of the most well-known lipopeptides used in treating infections is daptomycin ( Figure 5) [53].…”
Section: Antimicrobial Materialsmentioning
confidence: 91%
“…This combines to cause cell death. The self-assembly of daptomycin was studied outside of the cell and it was shown to aggregate into micelles [53]. This aggregation process may be correlated to its excellent antimicrobial activity.…”
Section: Antimicrobial Materialsmentioning
confidence: 99%
“…An example is daptomycin, produced by the Gram positive bacterium, Streptomyces roseoporous, which is used to treat MRSA and self-assembles into micelle structures. 23,24 Synthetic amphiphilic lipopeptides tend to be based on a bio-derived sequence, often containing a linear peptide head group with 1-3 (usually palmitoyl) lipid chains attached. An example is Toll-like receptor agonists.…”
mentioning
confidence: 99%